2007
DOI: 10.1175/mwr3441.1
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic Quantitative Precipitation Forecasting Using Bayesian Model Averaging

Abstract: Bayesian model averaging (BMA) is a statistical way of postprocessing forecast ensembles to create predictive probability density functions (PDFs) for weather quantities. It represents the predictive PDF as a weighted average of PDFs centered on the individual bias-corrected forecasts, where the weights are posterior probabilities of the models generating the forecasts and reflect the forecasts' relative contributions to predictive skill over a training period. It was developed initially for quantities whose P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
355
1
6

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 357 publications
(366 citation statements)
references
References 33 publications
(30 reference statements)
4
355
1
6
Order By: Relevance
“…How many and which such quantiles will yield best results could be investigated in any given instance. Similarly, the forms of the function f (x) (Equation (8)) involving the GFS ensemble mean that were tried included using √ x ens or x ens only, whereas other authors (Hamill et al, 2008;Sloughter et al, 2007) have reported that better results were obtained with different transformations of the ensemble-mean precipitation predictor. Similarly, no exploration of the use of other predictors (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…How many and which such quantiles will yield best results could be investigated in any given instance. Similarly, the forms of the function f (x) (Equation (8)) involving the GFS ensemble mean that were tried included using √ x ens or x ens only, whereas other authors (Hamill et al, 2008;Sloughter et al, 2007) have reported that better results were obtained with different transformations of the ensemble-mean precipitation predictor. Similarly, no exploration of the use of other predictors (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The conditional PDF (P i (y|f i , D)) denotes the posterior distributions of y given model prediction and observations, which is approximated by a normal distribution with mean (f i ) and standard deviation (σ i ). The assumption of normal distribution could be inappropriate for soil moisture primarily driven by precipitation, while the gamma distribution is more reasonable to represent the highly skewed predictive distribution of soil moisture [Sloughter et al, 2006]. However, when we tested the two assumptions (normal and gamma distribution), the assumption of normality improved more the BMA method for soil moisture prediction.…”
Section: Bayesian Model Averaging Scheme Based On the Land Surface Wementioning
confidence: 95%
“…Precipitation is not normally distributed, and here normal distributions have been replaced either by gamma (Wilks, 2006;Sloughter et al, 2007) or log(gamma) distributions. In each case the uncertainty of the day is defined by a gamma G(α, β), whose parameters α and β are determined numerically from the expectation m and standard deviation s (the notation G(m, s) is used hereafter for G (α(m, s), β(m, s))).…”
Section: Synthetic Data Experiments Set-upmentioning
confidence: 99%